Komposisi Diatom (Bacillariophyceae) Perifitik pada Substrat Kaca di Sungai Kapuas Kecil Kota Pontianak Kalimantan Barat - Tri Rima Setyawati, Rizki Aprilliani Rafdinal (Universitas Tanjungpura, 2018)
Periphytic diatom (Bacillariophyceae) is diatom that lives attach on a substrate and it was dependent on the environmental conditions in an aquatic ecosystem. This study was aimed to determine the composition of periphytic diatom (Bacillariphyceae) on glass substrate and the condition of physical chemical water in Kapuas Kecil River. This study was conducted from September to December 2017. The sampling stations were chosen by purposive random sampling method and divided into four stations. At each station in the river were installed 5 baskets each with 5 glass slides. Samples were collected from three baskets with sampling intervals on day 2, 5, 10, 15, and 20. The result shows that the composition of periphytic diatoms (Bacillariophyceae) in Kapuas Kecil River consists of 29 genera from 2 orders (Pennales and Centrales) and 12 families. The most commonly genera found of periphytic diatom were Eunotia, Gomphonema, Frustulia and Nitzschia.